2015
DOI: 10.25242/885x4102014186
|View full text |Cite
|
Sign up to set email alerts
|

Uso Do Silicato De Cálcio Na Correção Da Acidez Do Solo E No Desenvolvimento Da Brachiaria Ruziziensis L.

Abstract: O trabalho avaliou o efeito das doses de silicato de cálcio aplicadas superficialmente no solo afim  de tornar uma nova fonte para correção da acidez do solo e outros atributos químicos do solo e manutenção dos níveis de Si adequados para a planta de Brachiaria ruziziensis L e no desenvolvimento da Poaceae cultivado em casa de vegetação.  Utilizou-se o delineamento inteiramente casualizado em um experimento simples com seis tratamentos e quatro repetições cada, totalizando 24 unidades experimentais. Foram comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…Isso mostra o aumento da disponibilidade de Si no solo e a neutralização da acidez trocável (Al +3 ) e parte da acidez ativa (H + ). Silva et al (2014) trabalhando com Brachiaria ruziziensis L. observaram o aumento do pH do solo utilizando doses de 0 a 3,2 t ha -1 de silicato de cálcio e magnésio, o mesmo saindo de 6,08 para 6,73.…”
Section: Resultsunclassified
“…Isso mostra o aumento da disponibilidade de Si no solo e a neutralização da acidez trocável (Al +3 ) e parte da acidez ativa (H + ). Silva et al (2014) trabalhando com Brachiaria ruziziensis L. observaram o aumento do pH do solo utilizando doses de 0 a 3,2 t ha -1 de silicato de cálcio e magnésio, o mesmo saindo de 6,08 para 6,73.…”
Section: Resultsunclassified
“…studied under these conditions, as well as its effects on nutrient availability, especially micronutrients. Silva et al [22] concluded that excessive liming is less harmful to plants than not performing it, even if not recommended.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the application of agricultural gypsum, a by-product of phosphoric acid production, basically composed of calcium sulfate, is an alternative in the supply of Ca in depth and to reduce the contents of Al 3+ , limiting its toxic effect on root development (Silva et al 2015). Gypsum, therefore, has been used as a complementary input to lime, mainly because lime presents low soil mobility (Caires, Joris, and Churka 2011).…”
Section: Introductionmentioning
confidence: 99%